Qualidade de vida de mulheres no climatério residentes na área urbana da cidade de Coari-AM - Santos, Zaira Beatriz de Souza (Brasil, 2023)
Objective: to evaluate the quality of life of climacteric women living in the urban area of the city of Coari-Am. Methods: this is a cross-sectional, observational, descriptive and quantitative study. The study included 184 climacteric women aged between 45 and 65 years. Data collection was carried out using a standardized questionnaire developed referring to sociodemographic characteristics, lifestyle habits and clinical data. instrument of the Reproductive Aging Workshop - STRAW+10, Montreal Cognitive Assessment – MoCA, Menopause Rating Scale – MRS and the Utian Quality of Life Scale – UQOL. For categorical variables, the results were presented using relative and absolute frequency measurements, and for quantitative variables, mean calculations and respective standard deviations, version 24.0 for Windows® was used. SPSS® (Statistical Package for Social Sciences). Results: Among the interviewees, aged between 40 and 52 years, it was found that the majority are low-income women, with an intermediate level of education with up to 9 years of study and with steady partners, there was a prevalence of sedentary lifestyle in all menopausal stages, there was a very small percentage when using HRT and low adherence to treatments for symptoms, there was a prevalence of symptoms with severe intensity in all menopausal stages, the research revealed that the average of the participants had a good quality of life regardless of the menopausal stage, they had a moderate quality of life in the health and sexual domain.Conclusion: This study concludes that women residing in the municipality of Coari, Amazonas have a good quality of life, regardless of menopausal stages. On the other hand, the symptomatic manifestations of the climacteric were severely present for most women, as well as the high prevalence of a sedentary lifestyle.